Customer’s Perception Towards Petronas Lubricant Product In Kuching District / Mohammad Jais Daud - Daud, Mohammad Jais (2005)
Chapter One describes background and purpose, relevance and value for readers, and for other researchers. Beside that, the researcher formulates and defines the research problem. The problem definition is presented together with its research questions. The problem definition of this research is very substantial to be transformed directly into a framework for analysis and research questions are conducted to specify the problem definition. Besides that, the researcher also highlighted the limitations when conducting the research. Several definitions on terms used to give a clear understanding to the readers. The preliminary study made it possible to generate subsidiary questions that made the main questions easier to answer.